Hybrid Warfare: Above or Below the Threshold of Armed Conflict? - Marsili, M. (Honvédségi Szemle – Hungarian Defence Review, 2023)
The term “hybrid” gained widespread use in military and political discourse; it grabbed the headlines and eventually reached the general public. We refer to “hybrid warfare” or “hybrid conflict”, most likely without fully comprehending the term’s meaning and ramifications. The question is whether and when hybrid warfare should be regarded an armed attack that exceeds the threshold of damage and devastation caused by a kinetic action. The purpose of this paper is to shed light on the consistency of the growing doctrine of hybrid warfare with current international (humanitarian) law, beginning with a lexical and logical analysis of the words.